All-solution-processed BiVO4/SnO2 nanorods-axial-heterostructure with improved charge collection properties for solar water-splitting. Issue 22 (15th November 2022) - Jeong, Yoo Jae; Hong, Seo Yeong; Cho, In Sun
Abstract: Constructing heterostructure by coupling structures with a one-dimensional morphology is a promising method to enhance photoelectrodes' charge collection and light absorption properties for photoelectrochemical water splitting. Herein, we aimed to synthesize a BiVO4 (BVO)/Sb-doped SnO2 (SSO) nanorods-axial-heterostructure (NAH) via the facile solution-based methods of spin coating and hydrothermal growth. The thicknesses of the BVO layer and SSO nanorods were optimized by controlling the spin coating and hydrothermal growth cycles to maximize photocurrent generation. The resultant BVO/SSO NAH photoanode has a three times greater photocurrent density (2.3 mA cm −2 at 1.23 V vs. the reversible hydrogen electrode) than pristine BVO film (0.75 mA cm −2 ). This enhanced photocurrent density is attributed to the excellent charge collection (separation + transfer) property induced by the heterointerface (i.e., type II heterojunction) and the bottom single-crystalline SSO nanorods. Furthermore, the BVO/SSO NAH shows the highest photocurrent density of 3.2 mA cm −2, Faradaic efficiency of ∼93%, and long-term stability over 2 h via coupling with FeOOH oxygen evolution electrocatalyst. This study suggests that the axial heterostructure is a superior design platform for developing efficient photoelectrodes. Graphical abstract: Image 1